(untitled) (Web of Teachers: Inderscience Research, 2025)
Miniature art is East figurative of art important from directions one to be , refined taste, high aesthetic thought and patience demand to do creative is an activity . Modern training in the process this art to teach improvement — not only inheritance save , maybe him/her new to the generation innovative approach with to deliver that means.